SERVICE MANAGEMENT IN APOTEK P. BHAKTI KENCANA TOWARDS CUSTOMER SATISFACTION - Sobandi, Mamay Maulana (Journal of Pharmacopolium, 2019)
Service can basically be said to be an action and treatment or a way of serving others to fulfill what is their needs and desires. The level of customer satisfaction for a service can be measured by comparing the expectations of consumers to the quality of services desired by the reality they receive or feel. This study looks at the gap between the services provided and the services felt by consumers at the P. Bhakti Kencana Pharmacy. This research uses descriptive type. Descriptive method is a method of research carried out with the main purpose of making a description or description of a situation objectively. This study uses a type of primary data, namely the type of data obtained by direct collection by researchers such as the results of the questionnaire. The results of the study show the five dimensions namely Tangibles (Reality), Empathy (Sympathy), Reliability (Reliability), Responsiveness (Responsibility) and Assurance (Certainty). Keywords: Service quality, customer satisfaction, descriptive method.